Association of sexual problems with social, psychological, and physical problems in men and women: a cross sectional population survey. Issue 3 (1st March 1999) - Dunn, K M; Croft, P R; Hackett, G I
Abstract : STUDY OBJECTIVE: To investigate the association of sexual problems with social, physical, and psychological problems. DESIGN: An anonymous postal questionnaire survey. SETTING: Four general practices in England. PARTICIPANTS: 789 men and 979 women responding to a questionnaire sent to a stratified random sample of the adult general population (n = 4000). MAIN RESULTS: Strong physical, social, and psychological associations were found with sexual problems. In men, erectile problems and premature ejaculation were associated with increasing age. Erectile problems were most strongly associated with prostate trouble, with an age adjusted odds ratio of 2.6 (95% confidence intervals 1.4, 4.7), but hypertension and diabetes were also associated. Premature ejaculation was predominantly associated with anxiety (age adjusted odds ratio 3.1 (95% confidence intervals 1.7, 5.6)). In women, the predominant association with arousal, orgasmic, and enjoyment problems was martial difficulties, all with odds ratios greater than five. All female sexual problems were associated with anxiety and depression. Vaginal dryness was found to increase with age, whereas dyspareunia decreased with age. CONCLUSIONS: This study indicates that sexual problems cluster with self reported physical problems in men, and with psychological and social problems in women. This has potentially important consequences for the planning of treatment for sexual problems, and implies that effective therapy could have a broad impact on health in the adult population.